The Rights of Leave of Absence of Civil Servants - Bucaktepe, Adil (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
Civil officials have several rights conferred by the Constitution as well as by laws and regulations to facilitate the successful execution of their responsibilities. These rights encompass the entitlement to the appointment, provision of service and security, retirement, resignation, the ability to initiate a complaint or legal action, the formation of a trade union, collective bargaining, leave from employment, special considerations in prosecution and trial, protection against accusations and defamation, as well as the right to remuneration and travel expenses. This paper will succinctly examine the overarching rights of federal servants and will thoroughly analyze the